2013
DOI: 10.4028/www.scientific.net/amm.351-352.923
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization of Structural Stiffness of Offshore Platform with Rocking-Wall

Abstract: This paper presents a new offshore platform with rocking wall structure, and studies how to use the material more adequately by varying offshore platforms story rigidity. The results show that the greater the story stiffness, the more it can give full play to the material properties, as well as to improve the seismic capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Rocking walls have been used effectively in seismic retrofit of existing and historical structures [19] and a number of design configurations have been proposed in the literature and included in seismic design codes and recommendations. Studies showed that rocking wall systems can also greatly improve the seismic performance of offshore platforms [20,21]. However, and although the performance of these systems has been studied and documented in research and practice, some aspects of their behavior during rocking motion, particularly in the presence of nonlinear deformations in the soil, are still not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rocking walls have been used effectively in seismic retrofit of existing and historical structures [19] and a number of design configurations have been proposed in the literature and included in seismic design codes and recommendations. Studies showed that rocking wall systems can also greatly improve the seismic performance of offshore platforms [20,21]. However, and although the performance of these systems has been studied and documented in research and practice, some aspects of their behavior during rocking motion, particularly in the presence of nonlinear deformations in the soil, are still not fully investigated.…”
Section: Introductionmentioning
confidence: 99%